Biohybrid elastin-like venous valve with potential for in situ tissue engineering - González-Pérez, Fernando; Acosta, Sergio; Rütten, Stephan; Emonts, Caroline; Kopp, Alexander; Henke, Heinz-Werner; Bruners, Philipp; Gries, Thomas; Rodríguez-Cabello, J. Carlos; Jockenhoevel, Stefan; Fernández-Colino, Alicia (Frontiers in Bioengineering and Biotechnology, 2022)
Chronic venous insufficiency (CVI) is a leading vascular disease whose clinical manifestations include varicose veins, edemas, venous ulcers, and venous hypertension, among others. Therapies targeting this medical issue are scarce, and so far, no single venous valve prosthesis is clinically available. Herein, we have designed a bi-leaflet transcatheter venous valve that consists of (i) elastin-like recombinamers, (ii) a textile mesh reinforcement, and (iii) a bioabsorbable magnesium stent structure. Mechanical characterization of the resulting biohybrid elastin-like venous valves (EVV) showed an anisotropic behavior equivalent to the native bovine saphenous vein valves and mechanical strength suitable for vascular implantation. The EVV also featured minimal hemolysis and platelet adhesion, besides actively supporting endothelialization in vitro, thus setting the basis for its application as an in situ tissue engineering implant. In addition, the hydrodynamic testing in a pulsatile bioreactor demonstrated excellent hemodynamic valve performance, with minimal regurgitation (<10%) and pressure drop (<5 mmHg). No stagnation points were detected and an in vitro simulated transcatheter delivery showed the ability of the venous valve to withstand the implantation procedure. These results present a promising concept of a biohybrid transcatheter venous valve as an off-the-shelf implant, with great potential to provide clinical solutions for CVI treatment.